Book Review: The Passion Generation - Giovanni, Davin (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The book written by Grant Skeldon and Ryan Casey Waller focuses on the discussion of discipleship in the church. This is done because most churches and youth ministers do not really understand the meaning of discipleship itself. Discipleship is often thought of as small group ministry, mentoring, and doctrinal study classes. Through this book, Skeldon and Waller explain that discipleship is a person's habit of following others who are more spiritually advanced than themselves. That is why, the essence of discipleship is the relationship between the discipler and the young people as disciples. This works especially well with millennials whose lives are driven by purpose and desire. So, they can follow the person who guides them according to their wishes. In addition, Skeldon and Waller also explained that it is not only the church and youth ministries who play a role in discipling this millennial generation. However, parents must also have faith in Christ in order to guide their children in faith in Jesus Christ.